Beyond GnRH, LH and FSH: the role of kisspeptin on hypothalalmic-pituitary gonadal (HPG) axis pathology and diagnostic consideration - Sikandar Hayat Khan; Nayyer Chaudhry (Journal of the Pakistan Medical Association, 2021)
Kisspeptin as a neuropeptide was established initially as regulator GnRH pulse frequency and intensity. Over time it was recognized that the interaction are mediated through a specific receptor GPR54, which has also been found throughout the hypothalamic-pituitary-gonadal (HPG) axis. Further insights into the mechanisms leading to triggering of kisspeptin were identified to be both negative and positive feedbacks from gonadal steroids along with various internal metabolic alterations and environmental triggers in the shape of diet and lifestyle. More so it was identified that these Kisspeptin/GPR54 receptor interaction was also influenced by endocannabinoid (eCB) system, GABA-ergic neuronal outputs (GABA) and other chemical agents. The most influencing neuronal inputs modifying the release of kisspeptin were identified as group of neurons termed “KNDy” in the ARC nuclei. Based upon these discoveries, scientist attempted to evaluate kisspeptin as diagnostic marker for various diseases including precocious puberty, puberty confirmation, hypogonadism, infertility and polycystic ovarian Continuous...